The Use of Media in Language Teaching to Enhance Listening Skills in the Merdeka Curriculum - Tungkup, Miranda Kristin Lumban; Hutabarat, Esra Delima; Silitonga, Sarah Priscilla; Simanjuntak, Kesmi Veronika (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the use of media in language teaching to enhance students' listening skills within the framework of the Merdeka Curriculum. Listening is a fundamental skill in language acquisition, yet many students face challenges due to limited exposure to authentic listening materials. The integration of media such as audio recordings, podcasts, and interactive applications provides an immersive learning experience that fosters comprehension. This research employs a library research method, analyzing expert opinions and previous studies on the topic. Findings suggest that media use significantly enhances listening skills by providing real-life contexts, engaging learners, and catering to different learning styles. The study highlights the importance of media selection and its alignment with curriculum objectives to optimize learning outcomes.